Resíduos Medievais do Grotesco no Cordel de Metamorfose Contemporâneo - Silva, Cássia Alves da (2010)
This research, linked to line Literature and History, analyzes the grotesque residual in the metamorphosis’ drawstring contemporary. Use the Theory of Residuality, which deals with waste remaining from one culture into another, through processes of cultural hybridity, endoculturation and crystallization. The metamorphosis’ drawstring contemporary bring the grotesque in their two types: the terrificante and the comical. After the reading of eight drawstrings, we could see residues of the grotesque caused by the strong performance of the medieval Christian mentality in the culture of the Brazil’s Northeastern.